2019
DOI: 10.1111/gere.12358
|View full text |Cite
|
Sign up to set email alerts
|

Korean Americans in Los Angeles: Decentralized Concentration and Socio‐spatial Disparity

Abstract: This study analyses the socioeconomic and demographic make‐up of Koreans in Los Angeles metropolis, the largest hub of Koreans in the United States, to better understand the decentralized concentration of Koreans by addressing their within‐ and among‐group variations. By employing the rarely used measures of correspondence and typology analyses, we delineate the boundaries for Korean clusters using Getis and Ord G* local statistic, wherein each cluster's neighborhood and demographic characteristics are compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…We used ‘Tell-A-Friend about Data is Power’ as an ad campaign to communicate the importance of having data from Koreans for Koreans. This recruitment strategy, using language and race matched recruiters and researchers,35 62–64 would promote access to hard-to-reach KAs, and help participants to feel ‘listened to’ and show the ‘value of their contribution to the study’. As most KAs are connected and have ties to Korean churches or senior associations, we used a chain referral sampling method, such as other forms of respondent-driven sampling 35 65–68.…”
Section: Methodsmentioning
confidence: 99%
“…We used ‘Tell-A-Friend about Data is Power’ as an ad campaign to communicate the importance of having data from Koreans for Koreans. This recruitment strategy, using language and race matched recruiters and researchers,35 62–64 would promote access to hard-to-reach KAs, and help participants to feel ‘listened to’ and show the ‘value of their contribution to the study’. As most KAs are connected and have ties to Korean churches or senior associations, we used a chain referral sampling method, such as other forms of respondent-driven sampling 35 65–68.…”
Section: Methodsmentioning
confidence: 99%
“…Hidden within the data are underidentified and underserved students from the MENA and subgroups of Asian Americans. Sharma and Koh (2019) found that Koreans who reside in Orange County, CA, exhibit significant disparity in educational attainment when geographical concentration is taken into consideration. Although 85% of the southern Orange County Korean population had achieved an associate or higher degree, only 61% of the Koreatown residents had attained high school or lower education (Sharma & Koh, 2019).…”
Section: Disparities and Inequities Masked By Aggregated Datamentioning
confidence: 99%
“…Sharma and Koh (2019) found that Koreans who reside in Orange County, CA, exhibit significant disparity in educational attainment when geographical concentration is taken into consideration. Although 85% of the southern Orange County Korean population had achieved an associate or higher degree, only 61% of the Koreatown residents had attained high school or lower education (Sharma & Koh, 2019). This is yet another example of within group disparity that is masked by prevalent classification and general perception.…”
Section: Data Aggregationmentioning
confidence: 99%
“…The conventional 30-percent threshold is often used by government entities for distinguishing households as being rent-burdened (Joice, 2014). O'Dell et al (2004) argue that any fixed thresholds may be inefficient for gauging affordability and they may mask structural conditions of housing and neighborhood characteristics concerning the quality of life (Sharma, 2016;Sharma & Koh, 2019). Also, this definition does not take into account local contexts and housing market scenarios, since spending more than 30 percent on housing may be quite common in some areas (e.g., Los Angeles or New York City).…”
Section: Problems With Fixed Thresholdsmentioning
confidence: 99%